A SOCIOLOGICAL ANALYTICAL APPROACH TO POLITICAL PARTICIPATION IN ALGERIA - Laid Ouarem,; Laid Salakdji,; Amel Labidi,; Boudjema Amara, (International Journal of Innovative Technologies in Social Science, 2025)
This study aims to analyze political participation in Algeria and the impact of the political system, civil society, and press freedom on this participation. The findings indicate that the political system has remained authoritarian despite reforms, limiting the effectiveness of political pluralism and maintaining elections as a tool for reproducing power rather than achieving democratic transformation. Civil society suffers from government intervention and limited resources, while press freedom remains restricted despite periods of openness. Due to the absence of effective participation channels, political violence has escalated, as seen in the events of October 1988 and the Black Decade. Meanwhile, the Amazigh issue has evolved from an elite-driven movement into a significant political cause, ultimately leading to its official recognition.